Design, Synthesis, Configuration Research, and In Vitro Antituberculosis Activities of two Chiral Naphthylamine Substituted Analogs of Bedaquiline. (17th May 2016) - Wang, Zhiqiang; Li, Linwei; Zhou, Zhixu; Geng, Yiding; Chen, Yu; Sun, Tiemin
Abstract : Two chiral naphthylamine‐substituted analogs of Bedaquiline were selected from a series of compounds designed as anti‐tuberculosis drugs based on thestructure activity relationship of bedaquiline for synthetic and stereochemical research. The compounds were synthesized from the chiral precursors for the first time, and their absolute configurations were determined by electronic circular dichroism and quantum chemical calculations. Conformational analyses were performed on the compounds to find the stable conformers and get better predicted results. In addition, the in vitro antituberculosis activities of the two compounds were investigated. Abstract :